REPRESENTASI DI MEDIA SOSIAL SEBAGAI PEMBENTUK IDENTITAS BUDAYA POPULER - Yofiendi Indah Indainanto; Faiz Albar Nasution (Universitas Bunda Mulia, 2020)
ABSTRACTThe purpose of this study is to describe the process of forming a popular culture of coffee as a lifestyle of adolescents through representation on social media, and the relationship of power relations in the process. A digital pop culture is a form of popular culture that is formed by the development of technology through user interaction activities. The Instagram @filosofikopi account is very popular among coffee lovers and is a reference for teens to get to know the latest coffee style. Often it is used as a means to instill consumptive ideologies that are displayed naturally. The method used is a qualitative descriptive object with the Instagram account @filosofikopi. The concepts used are cultural commodification, and presentation of Erving Goffman to explain the post. The results of the research, popular culture is formed starting from the digital exploration activity stored from algorithmic data which has an impact on generating similar posts. The @filosofikopi account forms ideological standards through transactional posts that lead to the purchase of products and images that are displayed modernly with young people as objects of an image. The dominant self-presentation is shown by presenting objects of pleasure that lead to the inculcation of consumptive ideology.Keywords: Popular Culture, Commodification, Social Media, Instagram, filosofikopi ABSTRAKTujuan penelitian ini mendiskripsikan proses pembentukan budaya populer ngopi sebagai gaya hidup remaja melalui representasi di Media sosial, dan hubungan relasi kuasa dalam prosesnya. Digital pop culture merupakan bentuk budaya populer yang terbentuk dengan adanya perkembangan teknologi melalui aktivitas interkasi pengguna. Akun Instagram @filosofikopi sangat populer dikalangan pencinta kopi dan dijadikan refrensi bagi remaja untuk mengetahui gaya ngopi terkinian. Seringkali itu, dijadikan sarana untuk menanamkan ideologi konsumtif yang ditampilkan secara natural. Metode yang digunakan diskriftif kualitatif dengan objek akun Instagram @filosofikopi. Konsep yang digunakan komodifkasi kultural, dan seft presentation dari Erving Goffman untuk menjelaskan postingan. Hasil penelitian, budaya populer terbentuk bermulai dari aktivitas penjelajahan digital tersimpan dari data alogaritma yang berdampak pada memunculkan postingan serupa. Akun @filosofikopi membentuk standar ideologi melalui postingan transaksional yang mengarah pada pembelian produk dan citra yang ditampilkan moderen dengan anak muda sebagai objek citra . Presentasi diri yang dominan ditunjukan dengan menampilkan objek kesenangan yang mengarah pada penanaman ideologi konsumtif.Kata Kunci: Budaya Populer, Komodifikasi, Media Sosial, Instagram, Filosofi Kopi